The impact of the encouraging-activating-involving-assiting activities on writing proficiency and self-regulated learning = - Nguyễn, Duy Khang (Can Tho University, 2009)
This study investigated the impact of Encouraging-Activating-Involving-Assisting (EAIA) activities on the learners writing and their self-regulation. The researcher developed these EAIA activities with an aim to improve learners writing performance and their self-regulation in learning to write.